UN Peacekeeping mission in conflict zone: an analysis of the Implementation on the Responsibility to Protect (R2P) doctrine and resolution - Mohamad Zainuddin, Mohd Safwan Syahmi; Mahamad Aziz, Farhatul Mustamirrah (Faculty of Administrative Science and Policy Studies, 2025)
For the past of 76 years, the United Nations has been a vital force in helping to prevent and resolve conflicts around the globe. UN Peacekeeping missions have played a crucial role in the implementation doctrine of the Responsibility to Protect (R2P) in conflict zones, providing a platform for countries to work together and build peace. The objective of the study is to identify the roles and responsibilities of various actors in the implementation of R2P, analyse the challenges faced in the operation of R2P in conflict zones, and evaluate ways to improve the effectiveness of the UN peacekeeping mission in the R2P implementation process. Drawing on methods from discourse analysis, this study will be conducted through a qualitative methodology involving the study of important UN documents and also in- depth case studies. The analysis reveal that there are obstacles such as political constraints, insufficiently strong and clear mandates, lack of equipment resources and uneven integration among UN security council members. In addition, the policy of selective intervention in favour of powerful countries has affected application and consistency against the doctrine. As a conclusion, without overcoming the political and operational challenges, the effectiveness of R2P will remain compromised.